A complication of the rotator cuff with superior humeral paralyses: a myth of the deltoid muscle and the mechanics of the humeroscapular joint - Prudnikov, Oleg; Prudnikov, Yevgeny; Prudnikov, Dmitriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The authors examined 97 different damages in the shoulder joint region, including neurological, traumatic and mixed ones. It was revealed that isolated “axillary paralysis” (12 cases) did not cause any motor disturbances, except for inconstant weakness of extension (retroversion) and internal rotation of the arm, and preservation of the suprascapular nerve ensured active movements of the humeroscapular joint even in total brachial plexitis. It turned out that in case of deltoid muscle paralysis even a partially damaged rotatory cuff was sometimes able to abduct the arm. Isolated suprascapular paralysis resulted in a complete loss of function of the humeroscapular joint. Operations were made on 71 patients with complete or partial ruptures of the rotatory cuff, complicated by “axillary paralysis” separately or as by a component of brachial plexitis (including 40 cases of the so-called “terrible triad” of the shoulder joint). Surgical restoration of the rotatory cuff made it possible to receive 58 excellent and good results, including 7 patients, whose deltoid muscle paralysis proved to be irreversible. On the basis of their results the authors drew a conclusion that the rotatory cuff played the leading part in movements of the humeroscapular joint, the supraspinous muscle and suprascapular nerve serving as keys to diagnosis of superior brachial paralyses.